Incorporation of dietary fibre-rich oyster mushroom (Pleurotus sajor-caju) powder improves postprandial glycaemic response by interfering with starch granule structure and starch digestibility of biscuit - Sze, Han Ng; Sathyasurya, Sathyasurya Daniel Robert; Ahmad, Wan Amir Nizam Wan; Rosli, W. I. Wan (2017)
The purpose of this study was to determine the effects of Pleurotus sajor-caju (PSC) powder addition at 0, 4, 8 and 12% levels on the nutritional values, pasting properties, thermal characteristics, microstructure, in vitro starch digestibility, in vivo glycaemic index (GI) and sensorial properties of biscuits. Elevated incorporation levels of PSC powder increased the dietary fibre (DF) content and reduced the pasting viscosities and starch gelatinisation enthalpy value of biscuits. The addition of DF-rich PSC powder also interfered with the integrity of the starch granules by reducing the sizes and inducing the uneven spherical shapes of the starch granules, which, in turn, resulted in reduced starch susceptibility to digestive enzymes. The restriction starch hydrolysis rate markedly reduced the GI of biscuits. The incorporation of 8% PSC powder in biscuits (GI = 49) could be an effective way of developing a nutritious and low-GI biscuit without jeopardizing its desirable sensorial properties.